The role of diversity in complex ICA algorithms for fMRI analysis - Du, Wei; Levin-Schwartz, Yuri; Fu, Geng-Shen; Ma, Sai; Calhoun, Vince D.; Adalı, Tülay (Journal of neuroscience methods, 2016)
•Most ICA algorithms used for fMRI analysis make several simplifying assumptions.•We use CERBM and an MST-based analysis to exploit all information in fMRI data.•Our method finds more meaningful discriminative components than current methods.•General ICA algorithms achieve superior performance in the analysis of fMRI data. The widespread use of data-driven methods, such as independent component analysis (ICA), for the analysis of functional magnetic resonance imaging data (fMRI) has enabled deeper understanding of neural function. However, most popular ICA algorithms for fMRI analysis make several simplifying assumptions, thus ignoring sources of statistical information, types of “diversity,” and limiting their performance. We propose the use of complex entropy rate bound minimization (CERBM) for the analysis of actual fMRI data in its native, complex, domain. Though CERBM achieves enhanced performance through the exploitation of the three types of diversity inherent to complex fMRI data: noncircularity, non-Gaussianity, and sample-to-sample dependence, CERBM produces results that are more variable than simpler methods. This motivates the development of a minimum spanning tree (MST)-based stability analysis that mitigates the variability of CERBM. In order to validate our method, we compare the performance of CERBM with the popular CInfomax as well as complex entropy bound minimization (CEBM). We show that by leveraging CERBM and the MST-based stability analysis, we are able to consistently produce components that have a greater number of activated voxels in physically meaningful regions and can more accurately classify patients with schizophrenia than components generated using simpler models. Our results demonstrate the advantages of using ICA algorithms that can exploit all inherent types of diversity for the analysis of fMRI data when coupled with appropriate stability analyses.